A case of receptive amusia with prominent timbre perception defect. Issue 7 (July 1982) - Mazzucchi, A; Marchini, C; Budai, R; Parma, M
Abstract : A patient with a right temporal lesion is described who, in recognising sounds and noises, complained of deficits which seemed to be most evident when sounds and noises could be recognised mainly by timbre whereas no deficit was noticed when pitch and rhythm were the main indicators. In addition, some global distortions in musical appreciation were complained of and described as "resonance" or "loss of aesthetic pleasure".